RANCANG BANGUN SISTEM PEMBELAJARAN E-LEARNING BERBASIS WEBSITE PADA SPS TAAM AL-MUTTAQIN DEPOK - Ali Hakim Alfaroshi (2023)
The application of a website-based E-learning learning system is in an effort to improve the quality of learning at home, therefore supporting facilities and media are needed to teach PAUD teachers. with this learning system can help parents of students in providing teaching at home to help students in the learning process. In conducting this research the authors used the waterfall method because by using this method the process flow would run better because the system was designed according to the sequence of stages by stages. The system runs in teaching and learning activities at SPS TAAM Al-Muttaqin Depok still uses a convention system which sometimes is still ineffective because in this case there are limited materials and time which is only available during study hours resulting in a lack of learning interaction- Based on the findings in the research conducted by the authors it can be concluded that the website-based learning system can be used and functions as it should, namely it can assist parents of students in using the learning system as a learning medium that can support the teaching and learning process at home which is easily accessible as long as it has an internet connection and can be accessed anywhere.